Reaction of 2-naphthol with activated sludge - Komers, Karel (Univerzita Pardubice, 2000)
In a batch stirred isothermal reactor the biochemical reaction has been studied of water solution of 2-naphthol (BN) and activated sludge (AS) adapted to BN at aerobic conditions in the BN concentration range S(0) = 0.5 - 2 mmol dm -3, AS concentration range (wxpressed as the weight of dry biomass in the unit of the reaction volume) X0 = 0.1 - 4 g dm -3 and temperature range 11 - 40 °C. The decomposition of BN in the reaction mixture can be described as a reaction of zero order in BN and probably 1st order in AS if the ratio of initial concentrations p = X0/S0 is greater than 0.6 g AS per mmol BN. At lower p values the reaction order in BN fluctuated between 0 and 2. The concentration of AS was practically constant during every experiment, the concentration of oxygen dissolved in the raction mixture decreased by a reaction of zero order. In addition to the decomposition of BN a red dinaphthol derivative is formed as a side product. Its concentration increases at higher temperature and smaller p. The rate constant of the BN decomposition increased from k=0.23 at 11°C to k = 0.68 mmol S g-1 Xh-1 at 30°C. In this temperature interval the Arrhenius equation between k and temperature is fulfilled. The temperature above 40°C denaturates AS and stops the decomposition of BN.
Keywords: biochemické reakce; aktivované kaly; 2-naftol